A review of Afrotropical Perasis Hermann, 1905(Diptera: Asilidae: Laphriinae) - Londt, Jason G.h. (Zootaxa, 2007)
Afrotropical species of Perasis Hermann, 1905 are reviewed. The two species known from the region are P. transvaalensis Ricardo, 1925 from Southern Africa (South Africa) and P. carpenteri Oldroyd, 1970 from East Africa (Uganda and Burundi). A lectotype is designated for P. transvaalensis. Illustrations of the genitalia of these closely similar species show them to be distinct. New records of P. transvaalensis provide a better understanding of the distribution of this rarely encountered grassland / savannah species, and it is probable that Afrotropical species may be associated with river margins.